x+(3x-2)+(4x-4)=

Simple and best practice solution for x+(3x-2)+(4x-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(3x-2)+(4x-4)= equation:


Simplifying
x + (3x + -2) + (4x + -4) = 0

Reorder the terms:
x + (-2 + 3x) + (4x + -4) = 0

Remove parenthesis around (-2 + 3x)
x + -2 + 3x + (4x + -4) = 0

Reorder the terms:
x + -2 + 3x + (-4 + 4x) = 0

Remove parenthesis around (-4 + 4x)
x + -2 + 3x + -4 + 4x = 0

Reorder the terms:
-2 + -4 + x + 3x + 4x = 0

Combine like terms: -2 + -4 = -6
-6 + x + 3x + 4x = 0

Combine like terms: x + 3x = 4x
-6 + 4x + 4x = 0

Combine like terms: 4x + 4x = 8x
-6 + 8x = 0

Solving
-6 + 8x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + 8x = 0 + 6

Combine like terms: -6 + 6 = 0
0 + 8x = 0 + 6
8x = 0 + 6

Combine like terms: 0 + 6 = 6
8x = 6

Divide each side by '8'.
x = 0.75

Simplifying
x = 0.75

See similar equations:

| -40/21=x | | X+2y=145 | | 7(b+2)=4(b+2) | | 24x+4(34-x)=10 | | 2*X*X=30 | | 1/4(6-2)+1/5(2+8)=x | | 0.6X-0.2X=-20 | | 6(3(1+4(2+5)))=x | | 2p^2-17=-21 | | 8t+19=15 | | log(8x+12)=2 | | 3x-11=2x+8 | | 3(3-2)=2x-1 | | x-33/4=1/18 | | Cos^2a-7cosa-1=0 | | 3(7k^2+k)-5k=x | | Y=2x^2-2-7 | | 14+2n=44 | | 9x^2+15x+12=0 | | (5n+5)(2)= | | X+y+z=2x+4y+25z | | 12x=4(2x+1) | | (7m+6)-(3m-5)= | | 7x-16=9x-34 | | 4*p-p=-9 | | 2x^2+2y^2-28x+12y+114=0 | | (12x8/4-4) | | 2x+3y=35-x | | 2x^2+-7x+10.34=0 | | M+6=3M-4 | | -125=-5(1+8x) | | 5(5v-7)=-135 |

Equations solver categories